2007
DOI: 10.1038/ng.2007.49
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of high-flux-control genes of yeast through competition analyses in continuous cultures

Abstract: Using competition experiments in continuous cultures grown in different nutrient environments (glucose limited, ammonium limited, phosphate limited and white grape juice), we identified genes that show haploinsufficiency phenotypes (reduced growth rate when hemizygous) or haploproficiency phenotypes (increased growth rate when hemizygous). Haploproficient genes (815, 1,194, 733 and 654 in glucose-limited, ammonium-limited, phosphate-limited and white grape juice environments, respectively) frequently show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(146 citation statements)
references
References 18 publications
6
137
2
1
Order By: Relevance
“…Although a tRNA deletion resource has already been developed and has revealed interesting and distinct cellular responses to the deletion of tRNA families (Bloom-Ackermann et al 2014), it cannot be used for large-scale studies with pooled strains, since the deletion strains are not barcoded. In this respect our collection is a step forward, and will allow comprehensive genome profiling of cellular fitness in different environments (Delneri et al 2008). The list of common and unique tRNAs deleted in the two collections is provided in Supplemental Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a tRNA deletion resource has already been developed and has revealed interesting and distinct cellular responses to the deletion of tRNA families (Bloom-Ackermann et al 2014), it cannot be used for large-scale studies with pooled strains, since the deletion strains are not barcoded. In this respect our collection is a step forward, and will allow comprehensive genome profiling of cellular fitness in different environments (Delneri et al 2008). The list of common and unique tRNAs deleted in the two collections is provided in Supplemental Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion strain collections in the yeast Saccharomyces cerevisiae (S. cerevisiae) have proven to be an essential resource for furthering our knowledge of protein encoding gene function and for understanding phenotypic plasticity (Winzeler et al 1999;Giaever et al 2002;Delneri et al 2008;Bivi et al 2009;Paget et al 2014). Barcoded deletion strains have allowed numerous informative genome-wide phenotypic screens, synthetic genetic array (SGA) analysis , and chemogenomic screens (Giaever and Nislow 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1826 haplosufficient genes were identified using this definition. Although a haploinsufficient gene may become haplosufficient and vice versa when the environment changes, a recent study showed that haploinsufficiency is quite stable, at least among the nutritional environments tested (Delneri et al 2008). In other words, genes that are haploinsufficient in YPD are likely to be haploinsufficient in the yeast's natural environment as well.…”
Section: à10mentioning
confidence: 99%
“…This concept probably arises from the fact that inbreeding depression is cumulative over generations until it stabilizes but will be reversed immediately upon outcrossing to a different strain (Darwin, 1876). However, through the decades, examples of single gene heterosis have been documented, most notably by cases in Arabidopsis (Redei, 1962), cereals (Gustafson, 1946;Dollinger, 1985), and yeast (Delneri et al, 2008). Analyses of introgression lines of portions of the genome of a wild tomato species into domesticated tomato are most readily interpreted as due to the action of single genes (Semel et al, 2006).…”
Section: Despite the Multigenic Nature Of Heterosis Single Genes Or mentioning
confidence: 99%